Bangladesh and the Gulf War: response of a small state - Hossain, Ishtiaq (Pakistan Institute of International Affairs, Karachi, Pakistan, 1997)
This paper, first of all analyzes the foreign policy response of Bangladesh to the Gulf crisis. It will also examine the impact of its Gulf policy on its domestic politics. This discussion will show that even in a small country, major foreign policy issues can become a bone of contention in domestic politics. The second aim of this study is to explain how Dhaka took on the enormous task of repatriating its nationals from the war zone in the Gulf. The third major objective of this study is to assess the impact of the Gulf War on Bangladeshi economy.